Effect of various dopants on titanium dioxide nanorod arrays: A review / Mohd Rasydan Mustapha ... [et al.] - Mustapha, Mohd Rasydan; Malek, Mohd Firdaus; Mohamed Zahidi, Musa; Mohd Nor, Asiah; Mohamed, Ruziana; Asli, Noor Asnida; Ahmad, Mohd Khairul; Mahmood, Mohamad Rusop (Universiti Teknologi MARA Shah Alam, 2023)
In recent years, titanium dioxide (TiO2) has emerged as one of the most exceptional nanomaterials, attracting interest from experts throughout the globe. In addition to having a band gap of 3.2 eV, TiO2 has outstanding optical, structural, electrical, and photocatalytic capabilities that may be used in the semiconductor industry. However, because of its weak conductivity and capacitance, TiO2 has not been able to reach its full potential. In order to realise its full potential, researchers have devised a variety of methods, including hydrothermal deposition, sol-gel-assisted template deposition, chemical vapor deposition, electrochemical anodisation, hydrothermal deposition, and metal oxide doping. Doping TiO2 with metal oxides has been shown to significantly enhance its properties, which may improve its qualities. The primary goal of this study is to provide an overview of various research studies on the influence of the metal oxide dopant on the final properties of titanium dioxide (TiO2) nanorod arrays.